Corporate governance in South African higher education institutions - Crous, Cornelie (University of the Free State, 2017)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 Several Universities in South Africa, namely the Tshwane University of Technology (TUT), the Walter Sisulu University (WSU), the Central University of Technology (CUT) and Vaal University of Technology (VUT), were placed under administration since 2011 because of poor administration and governance. Examples of the poor administration and governance practices include, among others, the appointment of Vice-Chancellors with questionable qualifications, the payment of exorbitant remuneration to Vice-Chancellors, malfunctioning of the Councils and accusations and rumours of corruption in the National Student Financial Aid Scheme (NSFAS). The continued national student protests in 2015 and 2016 calling for free and quality higher education have placed renewed focus on the problems experienced by Universities. The soundness of the application of corporate governance principles at Universities, therefore, needed to be investigated. Because of this need, the application of corporate governance principles at South African Universities was addressed in this study. The Regulations for Reporting by Public Higher Education Institutions of 2014 require Universities to disclose their application of the King III principles in their Annual Reports. Although these disclosure requirements provide detail disclosure guidance, no international best practices were included. No tool, instrument or framework could be found to test the Universities’ compliance with the Reporting Regulations and King III principles, which further necessitated this study. By using a qualitative research design, this study used a literature review to develop a framework. The framework was based on the guidance in the Reporting Regulations (which contains the principles of the King III Report), international best practices, and the King IV Report. The framework could be used to determine the level of compliance of disclosures found in the South African Universities’ Annual Reports. Although the implementation date of the King IV Report is 1 April 2017, some Universities were proactive in the application of the principles contained in the King IV Report. The developed framework, therefore, includes additional disclosures, contained in the King IV Report, that were excluded from the Reporting Regulations, as a proactive measure in assessing the disclosure of King IV principles in the Annual Reports of the South African Universities. This framework was used in the empirical portion of the study to analyse the Annual Reports of the South African Universities for the 2011 to 2015 financial years. A total of 113 Annual Reports were analysed against the framework. The framework included 536 items based on the Reporting Regulations of South Africa; 140 items related to the changes from King III principles, as contained in the Reporting Regulations, to the King IV Report; and sixty items based on international best practices. Findings of the study suggest that some Universities in South Africa are proactive in the implementation of the King IV Report, although the implementation date of this report is only 1 April 2017. The disclosures of the South African Universities’ application and compliance with corporate governance principles, according to both South African and international best practice, are lacking in detail. The absence of detail disclosures leads to the concerns about the disclosure practices at these Universities as well as the Universities’ commitment to transparency and accountability. The problems experienced in obtaining the Annual Reports of the Universities raise additional concerns in terms of the Universities’ commitment to transparency and accountability. These problems raise concerns as the Universities are largely funded by state subsidies, which make the Annual Reports of each University information that should be publicly available. The results of the application of the framework clearly indicate that South African Universities need to address the quality of the information contained in their Annual Reports. The Council and Committee members need to be better informed of what their duties and functions are in terms of the disclosures in the Annual Reports. Universities should also ensure that the individual, or group of individuals responsible for compiling the Annual Reports is fully aware of the details that should be included in the Annual Reports. The framework developed in this study can be used by the Department of Higher Education and Training, external auditors of the Universities as well as the Universities themselves, to determine the level of compliance with the disclosure recommendations for Annual Reports. It may further be used as a rating system to rate the South African Universities with regards to the application and disclosure of application of corporate governance principles, or as a warning system to indicate shortages in the corporate governance practices of Universities. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 ŉ Aantal Suid-Afrikaanse Universiteite, naamlik die Tshwane Universiteit van Tegnologie (TUT), die Walter Sisulu Universiteit (WSU), die Sentrale Universiteit van Tegnologie (CUT) en die Vaal Universiteit van Tegnologie (VUT) is sedert 2011 weens swak administrasie en beheer, onder administrasie geplaas. Voorbeelde van die swak administrasie en beheer is onder andere die aanstelling van Visie-Kanseliers met twyfelagtige kwalifikasies, die betaling van buitensporige vergoeding aan Visie-Kanseliers, wanfunksionering van Rade en aantygings en gerugte van korrupsie met betrekking tot die Nasionale Studente Finansiële Hulp Skema (NSFAS). Die voortslepende nasionale studente betogings van 2015 en 2016 wat oproepe van gratis en gehalte hoëronderwys laat hoor, het hernude fokus op die probleme wat deur Universiteite ondervind word, geplaas. ŉ Ondersoek na die grondige toepassing van korporatiewe beheerbeginsels deur Universiteite is daarom ook nodig. In die lig van hierdie behoefte verleen hierdie studie aandag aan die toepassing van korporatiewe beheerbeginsels aan Suid-Afrikaanse Universiteite. Die 2014 Regulasies vir Verslagdoening deur Openbare Hoër Onderwys Instellings vereis van Universiteite om hulle toepassing van die King III beginsels in hul Jaarverslae te openbaar. Alhoewel hierdie openbaarmakingsvereistes gedetailleerde riglyne bevat, is geen internasionale beste praktyk ingesluit nie. Geen hulpmiddel, instrument of raamwerk kon gevind word om Universiteite se voldoening aan die Verslagdoeningsregulasies en King III beginsels teen te meet nie, wat hierdie studie verder genoodsaak het. Hierdie studie benut ŉ kwalitatiewe navorsingsontwerp, saam met ŉ literatuuroorsig om ŉ raamwerk te ontwikkel. Die raamwerk is op die Verslagdoeningsregulasies (wat die beginsels van King III vervat, insluit), internasionale beste praktyke en die finale King IV Verslag gebaseer, wat gebruik kan word om die vlak van voldoening aan openbaarmakingsvereistes van Suid-Afrikaanse Universiteite, te bepaal. Alhoewel die implementeringsdatum van die King IV Verslag eers 1 April 2017 is, was sommige Universiteite pro-aktief in die toepassing van die beginsels soos vervat in die King IV Verslag. Daarom, as ŉ proaktiewe maatstaf vir die assessering van King IV beginsels in die Jaarverslae van Suid-Afrikaanse Universiteite, sluit die raamwerk wat ontwikkel is, addisionele openbaarmakings ingevolge die King IV Verslag, wat nie in die Verslagdoeningsregulasies ingesluit is nie, in. Hierdie raamwerk is tydens die empiriese ondersoek in die ontleding van Jaarverslae van Suid-Afrikaanse Universiteite vanaf 2011 tot 2015 finansiële jare, gebruik. Altesaam 113 Jaarverslae is ontleed ingevolge die raamwerk. Die raamwerk bestaan uit 536 items met betrekking tot die Suid-Afrikaanse Verslagdoeningsregulasies; 140 items met betrekking tot veranderinge tussen die King III (soos vervat in die Verslagdoeningsregulasies) en King IV Verslae; en sestig items gegrond op internasionale beste praktyke. Die bevindinge van die studie dui aan dat sommige Suid-Afrikaanse Universiteite proaktief is in die toepassing van die finale King IV Verslag, alhoewel die implementeringsdatum eers 1 April 2017 is. Die openbaarmaking van die Suid-Afrikaanse Universiteite se voldoening aan korporatiewe beheerbeginsels, volgens beide die Suid-Afrikaanse Verslagdoeningsregulasies en internasionale beste praktyke, ontbreek ten opsigte van detail. Die afwesigheid van detail openbaarmaking wek kommer oor die openbaarmakingspraktyke van hierdie Universiteite sowel as die Universiteite se toewyding tot deursigtigheid en aanspreeklikheid. Die probleme wat ervaar is met die verkryging van die Jaarverslae van Universiteite het addisionele kommer rakende Universiteite se toewyding tot deursigtigheid en aanspreeklikheid na vore laat kom. Die probleme is kommerwekkend aangesien Universiteite grootliks deur staatsubsidies befonds word, wat beteken dat die inligting in die Jaarverslae van elke Universiteit, openbare inligting is. Die resultate van die raamwerk dui duidelik aan dat Suid-Afrikaanse Universiteite aandag moet verleen aan die gehalte van inligting wat in hulle Jaarverslae behoort vervat te wees. Die Raad- en Komiteelede behoort verder ook beter ingelig te wees rakende hulle pligte en verantwoordelikhede met betrekking tot openbaarmaking in die Jaarverslae en die individu, of groep individue, wat verantwoordelik is vir die samestelling van die Jaarverslae behoort ten volle ingelig te wees rakende die detail wat in die Jaarverslae ingesluit behoort te wees. Die raamwerk wat in die studie ontwikkel is, kan deur die Departement van Hoër Onderwys en Opleiding, Universiteite se eksterne ouditeurs asook die Universiteite self gebruik word ten einde die vlak van nakoming van die openbaarmakingsvereistes in Jaarverslae te bepaal. Dit kan verder ook gebruik word as ŉ graderingstelsel om die Suid-Afrikaanse Universiteite ten opsigte van hul toepassing van korporatiewe beheerbeginsels te gradeer, of as ŉ vroeë waarskuwingstelsel aan Universiteite oor tekortkominge in hulle korporatiewe beheer praktyke. ___________________________________________________________________
Thesis (Ph.D. (School of Accountancy))--University of the Free State, 2017
Keywords: Corporate governance; South African Universities; Annual Report disclosure; Reporting regulations; International best practice; King IV report; King III report; Education, Higher -- South Africa; Universities and colleges -- South Africa -- Administration